EORTC QLQ-15 PAL questionnaire as tool for determining the quality of life of patients with pancreas adenocarcinoma – preliminary study - Błaszczyk, Feliks; Susło, Robert; Nowak, Piotr; Beck, Bogusław; Drobnik, Jarosław (Family Medicine & Primary Care Review, 2017)
Background . In neoplastic diseases, quality of life often has to be balanced against duration of life, therefore adequate psychological support and optimal pain management are extremely important. The QLQ-C15 PAL questionnaire is recommended to be used for patients with advanced, incurable and symptomatic cancer, with an expected survival time of a few months, not undergoing anti-cancer treatment. Objectives . The aim of the study was to define, using the QLQ-C15 PAL questionnaire, the quality of life related needs of a group of patients with pancreas adenocarcinoma and to evaluate the questionnaire’s practical usefulness for palliative care monitoring and its ongoing improvement. Material and methods . A Polish translation of the QLQ-C15 PAL questionnaire was used in the year 2010 to estimate the quality of life of 26 patients with advanced stage pancreas adenocarcinoma, subjected to palliative care outside hospitals in the Lower Silesia region of Poland. Results . The majority of patients in the surveyed group considered their quality of life to be quite good, but the study pointed out 2 patients complaining of very poor quality of life, thus requiring a reevaluation of their needs and the strategy of their palliative support. Conclusions . The QLQ-C15 PAL questionnaire is a rapid and effective means to find out both the needs of particular patients and the characteristics of palliative care-covered patients groups. Its use enabled quick identification of those patients needing care adjustment. In cases when the questionnaire is filled in repeatedly over a longer period of time by the same patients, it can be useful in tracing the effectiveness of palliative care as measured by the patient’s quality of life.